International migration and social pain responses - Lu, M.; Hamamura, Takeshi; Chan, Y. (Pergamon Press, 2017)
International migration, arguably one of the most challenging life events, is an increasingly common psychological experience in the globalizing world. One novel approach in theorizing about wide-ranging psychological implications associated with international migration is to consider its effect in thwarting basic psychological needs. The focus of the current research is on a thwarted sense of control that migrants experience in their adjustment to a host society and its association with heightening pain responses. Among foreign-born residents in Canada (Study 1) and the United States (Study 2), a negative association was found between the participants’ identification with the host culture and their social pain responses. Study 2 supported the role of a diminished sense of control in mediating this association.